ANALISIS PENGARUH MODEL IKLAN TERHADAP PERILAKU PEMBELIAN REMAJA (Kasus Bintang Akademi Fantasi Indosiar) - Noviandra Krisjanti, W Mahestu (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2006)
This research analyzed the influences of Bintang AFI as advertising models on intention tobuy and buying recommendation. There are three independent variables, attractiveness,trustworthiness, and expertise. From the research, it is found that those three independent variables influence buying recommendation significantly. However, only one variable, it is the trustworthiness, that influences intention to buy.Keywords: intention to buy, buying recommendation, advertising model, teenagers